An analytical inquiry on timeshare research: A continuously growing segment in the hospitality industry. (January 2019) - Penela, Daniela; Morais, Ana Isabel; Gregory, Amy
Highlights: 67% of the total identified academic papers were published after the year 2000. 45 timeshare-dedicated theses/dissertations completed in the last decade. Timeshare research is being conducted in universities from 41 different countries. Abstract: This study provides an inquiry on research conducted on timeshare, through a collection of 133 academic papers from 69 journals, and 121 theses and dissertations from 29 countries. The results indicate an increasing trend in timeshare research, with 67% of papers published since 2000, and 37% of theses and dissertations in the last decade. The main contributors are Rosen College of Hospitality and Management, on the top for publication of academic papers, and University of Nevada, on first place for timeshare-related theses and dissertations. This first-ever far-reaching collection of literature allows the identification of key scholars and universities, and opens opportunities for exchange and cooperation within researchers to advance this body of literature. Finally, the contributions of this paper are not confined to timeshare research, as it draws attention to the importance of theses and dissertations, as a source of information that scholars are not using as much as they can.